2008
DOI: 10.1007/bf03346441
|View full text |Cite
|
Sign up to set email alerts
|

Generation and analysis of an androgen-responsive myoblast cell line indicates that androgens regulate myotube protein accretion

Abstract: Androgens have anabolic actions in skeletal muscle and could potentially act to: (a) increase proliferation of myoblasts; (b) delay differentiation to myotubes; and (c) induce protein accretion in post-proliferative myofibers. To identify the site of androgens action, we investigated the proliferative response of the C2C12 mouse myoblast cell line to testosterone and dihydrotestosterone (DHT) treatment. Neither androgens affected cell proliferation after up to 7 days treatment, nor was there a synergistic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Different studies have suggested that androgens act on satellite cells or myoblasts to increase the number of myonuclei (Mulvaney et al 1988, Joubert et al 1994, Joubert & Tobin 1995 or act on myofibers to increase protein content (Sheffield-Moore et al 1999, Ferrando et al 2002, Chen et al 2008, Ophoff et al 2009b. However, despite the fact that the AR is deleted by ≥93% in hind-limb muscles of both mAR ΔZF2 lines in our study, muscle mass is virtually normal with only relative muscle mass decreased in α-actin mAR ΔZF2 TA and soleus, but all other hind-limb muscles not different to AR lox controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have suggested that androgens act on satellite cells or myoblasts to increase the number of myonuclei (Mulvaney et al 1988, Joubert et al 1994, Joubert & Tobin 1995 or act on myofibers to increase protein content (Sheffield-Moore et al 1999, Ferrando et al 2002, Chen et al 2008, Ophoff et al 2009b. However, despite the fact that the AR is deleted by ≥93% in hind-limb muscles of both mAR ΔZF2 lines in our study, muscle mass is virtually normal with only relative muscle mass decreased in α-actin mAR ΔZF2 TA and soleus, but all other hind-limb muscles not different to AR lox controls.…”
Section: Discussionmentioning
confidence: 99%
“…Adult skeletal muscle fibers are terminally differentiated, and muscle repair and hypertrophy can occur either through an increase in the number of myonuclei, via activation of satellite cells (muscle stem cells) to proliferate as myoblasts, differentiate into myotubes and fuse with myofibers, or via an increase in protein content of postproliferative myofibers. While some studies have shown that androgens increase myoblast proliferation rate and/or delay differentiation (Powers & Florini 1975, Doumit et al 1996, Sinha-Hikim et al 2006, Diel et al 2008, others suggest the predominant actions are on protein accretion in myofibers (Ferrando et al 1998, Chen et al 2008. Maximal hypertrophic response to muscle overloading requires myofiber AR, but also involves other target cells (Ferry et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…C2C12 cells stably transfected with truncated ODC (pCMV-ODCT; kindly provided by Lisa Shantz, Department of Cellular and Molecular Physiology, Penn State Milton S. Hershey Medical Center) were generated as previously described (21). The ODC protein is truncated by 37 amino acids by insertion of a termination codon at position 426, which results in ODC protein with a extended half-life (41).…”
Section: Micementioning
confidence: 99%
“…To determine if ODC regulates proliferation, proliferating C2C12 myoblasts, which we previously used as a model of myoblast proliferation (21), were treated with difluoromethylornithine (DFMO; Chem-Impex), an irreversible and specific inhibitor of ODC. Myoblasts were seeded in proliferation medium for 1 h and then treated for 24, 48, or 72 h (n ϭ 4 -6/cell line), and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays were performed to measure myoblast number at each time point.…”
Section: Micementioning
confidence: 99%
“…In adapting muscle, satellite cells are activated, proliferate and subsequently fuse with muscle fibers [82]. Androgens regulate satellite cell activity through the androgen receptor but the fastest nongenomic effect of anabolic action has not been shown (reviewed in [83]). …”
Section: Satellite Cells and Anabolic Effectmentioning
confidence: 99%